Meeting the challenges and strategies regarding malaria elimination: qualitative evaluation of perceptions from a local population in Colombia - Knudson Ospina, Angélica; Simanca Castro, Elkin Leonardo; Barreto-Zorza, Yenny Marcela; Ospina Rodríguez, Olga Lucía; Parada Aguilar, María Alejandra; Perilla Roa, Daniel; Ariza-Araújo, Yoseth; Castillo, Carlos Felipe; Olaya Másmela, Luz Adriana; Apráez Ippolito, Giovanni; Piamba Dorado, Anderson Hair; Sánchez Pedraza, Ricardo; et al. (Frontiers in Malaria, 2024)
One Health" and "Social Determinants of Health" approaches are crucial for implementation of sustainable strategies for the control and elimination of infectious diseases such as malaria. These approaches highlight the importance of the social component in the design of elimination strategies, as well as the communities' involvement in the implementation of these measures at local levels. Qualitative analysis approaches for malaria research can be useful for assessing population acceptance of intervention measures and for addressing negative perceptions that can threaten the success of control goals by undermining the community's trust in interventions. In this paper, we explore some observations and interpretations from the qualitative content analysis of two openended questions about malaria, from a survey conducted between September and November 2016 in Guapi, a high risk transmission area in the Colombian Pacific Region. Using the spatial transmission unit concept for the analysis of the conditions and factors involved in malaria transmission under the "One Health" and "Social Determinants of Health" approaches, we reveal that responders' perceptions reflects both the need and requirement for continuous assistance to solve local problems and also a comprehensive problem-solving effort by the government that includes basic sanitation.From the analyses, we present a graphic model that illustrates how to address the problem of malaria control and elimination from the perspectives of the community's perceptions in Guapi, highlightingthe need for joint efforts of community, academy, and government to achieve the goal of controlling and eliminating malaria in the region.